Clot microatructure (dt) as a blomarker and measurement of thrombogenlcity in Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) - SURESH PILLAI (2024)
Introduction: Chronic obstructive pulmonary disease is an inflammatory condition of the lungs characterised by irreversible airway obstruction and impairment of gas exchange. Acute exacerbation is associated with an increased incidence of venous thromboembolism. The main aim of the study was to investigate whether patients with acute exacerbation were thrombogenic utilising the functional biomarker of clot microstructure, the fractal dimension (df). Methodology: The study recruited 30 stable patients from the chest clinic and 85 patients with acute exacerbation from the Emergency Department of a tertiary teaching hospital. One sample of blood was taken from stable group. Acute exacerbation group had four sampling points at 0 hours, 4-6 hours, 24 hours and 3-7 days. Results: The biomarker, df was significantly elevated in patients presenting with acute exacerbation when compared to stable group (1.71 ± 0.06 vs 1.69 ± 0.05, p=0.03). There was no significant increase in df across the four time points (p=0.28) in the acute exacerbation group. All inflammatory markers and fibrinolytic markers such as D-dimer were significantly higher in acute exacerbation group. Those who died during admission in the acute exacerbation group had significantly elevated df when compared to those who survived (1.76 ± 0.03 vs 1.71 ± 0.06, p=0.02) and binary regression analysis showed that df was a significant predictor of mortality (p=0.024). Conclusions: Patients with chronic obstructive pulmonary disease during exacerbation had denser and tighter clot microstructure as demonstrated by significantly elevated df when compared to stable group indicating that they were thrombogenic. This was due to profound inflammatory response and increased fibrin production. However, with appropriate treatments and prophylactic anticoagulation, there was no further increase in df which might explain low incidence of venous thromboembolism during admissions. Therefore, df is a useful biomarker that measures thrombogenicity, effect of treatment and predicts mortality in patients with acute exacerbation.